The Duration of Judicial Deliberation: Evidence from Belgium - Samantha Bielen; Wim Marneffe; Peter Grajzl; Valentina Dimitrova-Grajzl (Center for Economic Studies and ifo Institute (CESifo), 2016)
We utilize case-level data from a large Belgian court to study a policy-relevant but thus far empirically unexplored aspect of judicial behavior: the time that a judge takes to deliberate on a case before rendering a verdict. Exploiting the de facto random administrative assignment of filed cases among the serving judges and using survival analysis methods, we find that the duration of judicial deliberation varies not only with measures of case complexity, but also with judge and disputing party characteristics. We further find evidence consistent with the hypothesis that longer judicial deliberation improves the quality of judicial decisions.
Keywords: K40; K41; K49; 330; judicial deliberation; case-level data; survival analysis; speed-quality tradeoff; Belgium